Pengaruh Kualitas Produk, Harga, Dan Kualitas Pelayanan Terhadap Kepuasan Konsumen Pada Rumah Makan Dabu-Dabu Iris Fresh Wenang Manado - Gahensya Keloay; Wehelmina Rumawas; Sandra Asaloei (JURNAL ADMINISTRASI BISNIS, 2019)
This research was conducted in Dabu-Dabu Iris Fresh Restaurant, Wenang Manado, which aims to find out the 1) effect of product quality ; 2) price and ; 3) service quality on customer satisfaction in Dabu-Dabu Iris Fresh Restaurant, Manado, both individually and in groups. With the focus of the problem is whether product quality, price and service quality affect consumer satisfaction in Rumah Makan Dabu-Dabu Iris Fresh, Wenang Manado. the method used in this study uses quantitative descriptive methods and The population that came in the Dabu-Dabu Iris Fresh Restaurant, Manado Heritage is unknown, therefore the researcher took a sample of 50 respondents using a purposive sampling technique that is consideration of populations that are easily found and this research will only be given to visitors who have visited the House. Eating Dabu-Dabu Iris Fresh, Managing Manado at least 5 times, and the research method used is quantitative descriptive method. The analytical tool used in the data instrument test (validity and reliability test), classic assumption test (normality test, multicollinearity test and heteroscedasticity test), data analysis (multiple regression analysis, test t, F test and test coefficient of determination R2). Based on the t test obtained states that product quality has an influence on customer satisfaction individually. While price is the determination of the value of a product in the minds of consumers that must be paid by consumers to obtain a product of Dabu-Dabu Iris Fresh Restaurant, Wenang Manado. The service quality provided by Dabu-Dabu Iris Fresh Restaurant, Wenang Manado affects consumer satisfaction.